2004
DOI: 10.1111/j.1346-8138.2004.tb00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress‐Mediated Skin Damage in an Experimental Mobile Phone Model Can Be Prevented by Melatonin

Abstract: Most mobile phones emit 900 MHz of radiation that is mainly absorbed by the external organs. The effects of 900 MHz of radiation on fibrosis, lipid peroxidation, and anti-oxidant enzymes and the ameliorating effects of melatonin (Mel) were evaluated in rat skin. Thirty Wistar-Albino rats were used in the study. The experimental groups were the control group, the irradiated group (IR), and the irradiated+Mel treated group (IR+Mel). A dose of 900 MHz, 2 W radiation was applied to the IR group every day for 10 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 26 publications
4
21
0
1
Order By: Relevance
“…Malondialdehyde level was found to be increased in various organs of animals exposed to MWs (19)(20)(21)24,25) including liver (22,26,27). Our results show as well, that MDA levelsare increased in liver tissue of rats exposed to microwaves after prolonged exposition period (40 and 60 days).…”
Section: Disscusionsupporting
confidence: 69%
See 1 more Smart Citation
“…Malondialdehyde level was found to be increased in various organs of animals exposed to MWs (19)(20)(21)24,25) including liver (22,26,27). Our results show as well, that MDA levelsare increased in liver tissue of rats exposed to microwaves after prolonged exposition period (40 and 60 days).…”
Section: Disscusionsupporting
confidence: 69%
“…Catalase activity is found to be higher in organs of animals exposed to MWs (22,25).We also found higher catalase activity in irradiated animals. Catalase activity may be elevated as compensatory mechanism in animals exposed to MWs, due to microwave induced oxidative stress.…”
Section: Disscusionsupporting
confidence: 63%
“…The Nat1 gene encodes acetyltransferases (ATs) that can acetylate the endogenous arylalkylamines tryptamine, 5-hydroxytryptamine (serotonin), and 5-methoxytryptamine, the immediate precursor of melatonin. Melatonin response to electromagnetic fields has been discussed in the literature for a long time and some studies have indicated a potential of melatonin to suppress MW effects on brain, kidney, and skin of rats [Lai and Singh, 1997;Ayata et al, 2004;Oktem et al, 2005]. Recent evidence indicated a possible decrease in melatonin production among cellular telephone users [Burch et al, 2002].…”
Section: Discussionmentioning
confidence: 98%
“…On one hand -in fact -it has been argued that acute exposure between 1 and 4 h to the GSM-EMFs determines biological effects "in vitro" (Leszczynski et al, 2002;Nylund and Leszczynski, 2004;Sarimov et al, 2004;Buttiglione et al, 2007) as well as "in vivo" in animal models (Shallom et al, 2002;Ilhan et al, 2004) and humans (Moustafa et al, 2001;Ferreri et al, 2006). These effects have been ascribed to the modulation of dependent Na-K trans-membrane ionic channels (Cleary, 1995), the alteration of cellular homeostasis of Ca++ ion (Adey, 1981), the increase of cellular excitability, the activation of cellular response to stress (Tattersall et al, 2001;Ferreri et al, 2006) and to influences on cellular oxidative and biological reactions, particularly those related to aging processes (Moustafa et al, 2001;Irmak et al, 2002;Ilhan et al, 2004;Ayata et al, 2004;Oktem et al, 2005;Ozguner et al, 2005;Buttiglione et al, 2007). On the other hand, other evidence was not able to show that acute exposure to the GSM-EMFs could induce measurable biological effects on brain functioning in rest condition (Krause et al, 2000a).…”
Section: Introductionmentioning
confidence: 97%